The Importance of Inventory Management in Pharmaceutical Practice - Rachmat Hidayat; Irsan Saleh (Open Access Indonesia Journal of Social Sciences, 2020)
Efficient inventory management enhances gross profits and net profits by reducing the cost of procured pharmaceutical products and associated operational expenses. In addition, cash flow will improve upon saving on purchasing and storing less costly products. Such cash flow can be used to pay operational expenses and invest in other services. In addition to the negative impacts on financial outcomes from the pharmacy’s business perspective, inventory mismanagement could have deleterious corollaries on patient safety. Such outcomes can be attributed by the availability of expired, counterfeit, substandard, or spoiled products; unavailability of essential products; unclaimed prescriptions; and not updating formularies. From both financial and operational perspectives, efficient inventory management plays a great role in pharmacy practice. Thus, both methods of inventory management & methods of evaluating inventory management should be integrated into the curriculum of pharmacy programs, in addition to including them in the continuing education courses for registered pharmacists.